Gamma/Delta T Cells in the Course of Healthy Human Pregnancy: Cytotoxic Potential and the Tendency of CD8 Expression Make CD56+ γδT Cells a Unique Lymphocyte Subset - Nörenberg, Jasper; Jaksó, Pál; Barakonyi, Alíz (Frontiers in Immunology, 2021)
To date, pregnancy is an immunological paradox. The semi-allogenic fetus must be accepted by the maternal immune system, while defense against pathogens and immune surveillance cannot be compromised. Gamma/delta T cells are believed to play an important role in this immunological puzzle. In this study, we analyzed peripheral blood CD56+ γδT cells from pregnant women (1st, 2nd and 3rd trimester) and non-pregnant women by multicolor flow cytometry. Interestingly, γδT cells represent almost half of CD3+/CD56+ cells. Among γδT cells, the CD56+ population expands in the 2nd and 3rd trimester. CD56+ γδT cells maintained a predominantly CD4–/CD8– or CD8+ phenotype, while CD56– γδT cells were in similar rates CD4–/CD8– or CD4+ during pregnancy. Investigation of the lysosomal degranulation marker CD107a revealed a preserved elevated rate of potentially cytotoxic CD56+ γδT cells in pregnancy, while their cytotoxic strength was reduced. Furthermore, CD56+ γδT cells continuously showed a higher prevalence of PD-1 expression. CD56+ γδT cells’ rate of PD-1 increased in the 1st trimester and decreased hereafter back to normal level. We correlated the cytotoxic potential and the expression of the inhibitory immune checkpoint PD-1 and were able to demonstrate that highly cytotoxic cells within this CD56+ γδT population tend to express PD-1, which might allow the inhibition of these cells after binding its ligand in the placenta. These findings should support the understanding of the complex processes, which ensure the maintenance of pregnancy.